Correction: Comparative dissection of the peripheral olfactory system of the Chagas disease vectors Rhodnius prolixus and Rhodnius brethesi. - Florencia Campetella; Rickard Ignell; Rolf Beutel; Bill S Hansson; Silke Sachse (Public Library of Science (PLoS), 2022)
[This corrects the article DOI: 10.1371/journal.pntd.0009098.].